Willingness to pay for agricultural crop insurance in the northern EU. Issue 4 (28th October 2014) - Liesivaara, Petri; Myyrä, Sami
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the demand for crop insurance. Moreover, farmer willingness to pay (WTP) for crop insurance was derived. Factors affecting the demand were also examined in a country where crop insurance products are not currently available. Sensitivity analysis was conducted by studying the price-anchoring effect. Design/methodology/approach – Data from a choice experiment (CE) were analyzed with mixed logit models and the distribution of farmer WTP for crop insurance was derived. A split sample approach with varying premium vectors was used to analyze the price-anchoring effect. Findings – Demand was revealed for crop insurance products in Finland. The demand was higher among younger farmers and farms with more arable land. WTP for crop insurance products was very sensitive to the premium interval presented in the CE design. Research limitations/implications – The price-anchoring effect may disrupt the market development of crop insurance products, because insurance companies may take advantage of the lack of awareness among farmers of crop insurance pricing. Practical implications – The insurance product expected indemnity was a more important factor than the deductible in determining farmer WTP for crop insurance. Therefore, the 30 percent deductible level set for subsidized crop insurance products is not an obstacle for the development of such products in the EU. Originality/value – The study applied a well-known method (CE) to crop insurance in a country where these products are non-existent. The split sample approach was used to examine the price-anchoring effect on crop insurance.